PENGARUH PUPUK KANDANG AYAM TERHADAP SERAPAN NITROGEN OLEH TANAMAN KUBIS BUNGA (Brassica oleracea L.) PADA OXIC DYSTRUDEPTS LEMBANTONGOA - Asni Afianti Makka; Yosep Soge Patadungan; Sri Wahidah Prahastuti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
This research aimed to determine the effect of poultry manure on nitrogen uptake of cabbage (Brassica oleracea L.)plant grown on Oxic Dystrudpets Lembantongoa. This research used a Randomized Block Design (RBD) consisting of sevenrates of poultry manure i.e. Control, 10 t ha-1,  20 t ha-1, 30 t ha-1, 40 t ha-1,50 t ha-1, and60 t ha-1. Eachtreatmentwas replicated3 times, sothere were 21experimental units.If Analysis of variance of data showed a significant effect, then the data was tested further using honestly significant differenceat 5 % (HSD 5%). The results ofthis study indicatedthat the use ofvariousrates ofpoultry manure couldincreaseplant dry weightas shown bya linearequation y = 0.338x + 51.90 with R2 = 0.919, consistent withincreased levels ofNin theplant tissuewiththe linearequation y = 0,035x + 0,022 with R2 = 0,994 andN uptakewiththe equation        y = 0,026x - 0,055 (R2 = 0,985). The highestN uptakewas obtainedin theapplication of60tha-1poultry manure.Key words : Poultry manure, N uptake, Oxic Dystrudepts.